The Influence of the Quality of the School Quality Manual and Principal Supervision on Teacher Learning Innovation in Secondary Schools - Ruddy Hendriawan; Yulia Rahmawati; Henny Suharyati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to analyze the effect of the quality of educational quality manuals and principal supervision on teacher innovation in secondary school instruction. Amid ongoing curriculum reforms, many Indonesian schools still face challenges in fostering innovative teaching practices. This research applies a quantitative explanatory method with a Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach to test the influence of two independent variables: quality of the educational quality manual (X1) and principal supervision (X2), on the dependent variable: teacher instructional innovation (Y). The study was conducted at Sekolah Islam Cendekia—covering SD, SMP, and SMA levels—under the management of Yayasan Pribadi Kamila Cianjur, Indonesia, involving 40 respondents selected from this foundation, which has implemented both standardized educational quality manuals and active principal supervision. The results of the outer model analysis show that all indicators are valid (loading factors > 0.7) and reliable (AVE > 0.5, Composite Reliability > 0.9). The inner model results indicate a very high predictive power, where both X1 and X2 simultaneously explain 93.9% of the variance in teacher innovation (R2 = 0.939). Path coefficient testing revealed that the quality of the educational quality manual has a dominant and significant effect on teacher innovation (β = 0.529; p < 0.05), followed by principal supervision which also shows a strong and significant positive effect (β = 0.450; p < 0.05). These findings suggest that teacher innovation is primarily driven by the clarity of quality standards which provide a